The use of multiple sources of social information in contest behavior: testing the social cognitive abilities of a cichlid fish - Hotta, Takashi; Takeyama, Tomohiro; Heg, Dik; Awata, Satoshi; Jordan, Lyndon A.; Kohda, Masanori (Frontiers in Ecology and Evolution, 2015)
Theory suggests that living in large social groups with dynamic social interactions often favours the evolution of enhanced cognitive abilities. Studies of how animals assess their own contest ability commonly focus on a single cognitive task, and little is known about the diversity or co-occurrence of cognitive abilities in social species. We examined how a highly social cichlid fish Julidochromis transcriptus uses four major cognitive abilities in contest situations; direct experience, winner/loser effects, social eavesdropping and transitive inference (TI). We conducted experiments in which fish assessed the social status of rivals after either direct physical contests or observed contests. Individuals used direct information from a previous physical encounter to re-establish dominance without additional contact, but winner/loser effects were not observed. Social eavesdropping alone was ruled out, but we found that transitive reasoning was used to infer social dominance of other individuals of unknown status. Our results suggest that in stable hierarchical social groups, estimations of contest ability, based on individual recognition pathways such as TI and direct experience, are more prevalent than social eavesdropping or winner/loser effects. We suggest that advanced cognitive abilities might be widespread among highly social fishes, but have previously gone undetected.